Medieval Arles through the Lives of Its Founding Bishop - Herrick, Samantha Kahn (2024)
Texts recounting the careers of saints were foundational to Christian worship and historical construction in medieval Europe. They were also fluid, living works that evolved over time as individual saints’ stories were revised, adapted, and retold. These texts changed in response to changing contexts in which they were used and understood. This article undertakes a case study to see how the evolution of one urban saint’s legend reflects the history of that saint’s city. Specifically, it analyzes the numerous Latin and vernacular texts produced between the mid-fifth and late twelfth centuries that recount the deeds of Saint Trophimus, first bishop of Arles. It argues that shifts in the saint’s story reflect broad changes in the political, religious, and social life of Arles. It also demonstrates that the number of parties recounting the legend multiplied over time, and that dissonances within the story arose as these groups adapted the tale to their own interests.
Keywords: Bishops; Arles; France; Gaul; medieval Europe; Hagiography; urban history; Cities; Saints